Timing at peak lengths and forces of hip joint muscles during sprint running - Nagano, Y.; Higashihara, A.; Takahashi, K.; Fukubashi, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The biceps femoris is the most commonly injured muscle among the hamstring muscles (Woods et al., 2004). Increased biceps femoris muscle-tendon force carries the risk of hamstring strain injury. Moreover, it is possible that other hip joint muscles influence biceps femoris mechanics. The opposite iliacus are suggested to influence the mechanics of biceps femoris (Riley et al., 2010). The purpose of this study is to investigate the relation of muscle lengths and muscle-tendon forces of hip joint muscles during sprint running and particularly, to examine the relationships with the peak of biceps femoris muscle-tendon force. Methods: We obtained threedimensional kinematics during 1 running cycle from 8 healthy sprinters sprinting at maximum speed. These data were used to drive musculoskeletal models by using nMotion musculous (NAC Image Technology., Inc.JAPAN). Muscle lengths and muscle-tendon forces were calculated for iliacus, rectus femoris, gluteus maximus, biceps femoris, opposite iliacus, and opposite rectus femoris. The time at muscle lengths and muscle-tendon force peaks as percent running cycle were measured and compared with muscle-tendon force peak of biceps femoris by using Bonferroni multiple comparison test. Results: The peak muscle-tendon force of the biceps femoris occurred at 80.5 (2.9)% of the running cycle. It was significantly different from the peak muscle lengths of iliacus, rectus femoris, gluteus maximus, opposite iliacus, and opposite rectus femoris (p < 0.01, respectively) and the peak muscle-tendon forces of rectus femoris and opposite rectus femoris (p < 0.01, respectively). However, it was not significantly different from the peak muscle lengths of biceps femoris, peak muscle-tendon forces of opposite iliacus, and the second peak of iliacus and gluteus maximus. Discussion: The results of this study showed that the peak muscle-tendon force of biceps femoris synchronised with the peak muscle-tendon forces of opposite iliacus and the second peak of iliacus and gluteus maximus. A previous study reported that muscles in the lumbo-pelvic region had great influence on hamstring stretch (Chumanov et al., 2007). It is possible that the contraction and flexibility of these muscles influence the mechanics and injury risk of biceps femoris.